Development of Public Service Information System for Local Government - Riansyah; Elyandi, Juli; Saskia, Dwi Putri; Sinaga, Eki Rosnita; Matondang, Adinda Rizki Ramadhana; Padang, Ratnauli; Arnita, Vina (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to develop an innovative public service information system for local governments to improve efficiency and transparency. Using a mixed-methods approach, the study involved qualitative interviews with 50 local government officials to identify existing challenges and a quantitative survey with 200 citizens to measure satisfaction and service efficiency. The system is equipped with real-time application tracking, integrated data management, and automated notifications. Key findings show significant improvements in public service efficiency, with average turnaround time reduced from 5 to 2 days, and citizen satisfaction increased from 65% to 85%. Furthermore, the study emphasizes the importance of involving end-users in the development process, ensuring that their feedback is used for continuous system improvements that are relevant to user needs. In conclusion, the study shows that the developed system not only improves operational efficiency and transparency but also significantly increases public trust in local government services